2022
DOI: 10.1038/s41598-022-19643-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine laboratory biomarkers used to predict Gram-positive or Gram-negative bacteria involved in bloodstream infections

Abstract: This study evaluated routine laboratory biomarkers (RLB) to predict the infectious bacterial group, Gram-positive (GP) or Gram-negative (GN) associated with bloodstream infection (BSI) before the result of blood culture (BC). A total of 13,574 BC of 6787 patients (217 BSI-GP and 238 BSI-GN) and 68 different RLB from these were analyzed. The logistic regression model was built considering BSI-GP or BSI-GN as response variable and RLB as covariates. After four filters applied total of 320 patients and 16 RLB rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These findings align with prior research conducted by Guarno et al [7] . Similarly, an investigation by Daniela Dambroso et al [8] indicated that 47.7% of bloodstream infections were due to Gram-positive bacteria and 52.3% to Gram-negative bacteria, with the Enterobacteriaceae family, particularly E. coli (26.5%) andK. pneumoniae (19.7%), being the most prevalent.…”
Section: Discussionmentioning
confidence: 94%
“…These findings align with prior research conducted by Guarno et al [7] . Similarly, an investigation by Daniela Dambroso et al [8] indicated that 47.7% of bloodstream infections were due to Gram-positive bacteria and 52.3% to Gram-negative bacteria, with the Enterobacteriaceae family, particularly E. coli (26.5%) andK. pneumoniae (19.7%), being the most prevalent.…”
Section: Discussionmentioning
confidence: 94%
“…Another element influencing GNB infections is hemoglobin. Previous research has demonstrated a correlation between greater hemoglobin and a higher prevalence of GNB infections [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin is a peptide precursor of calcitonin, which is produced by the C-cells of the thyroid gland. Its serum levels rise rapidly in response to bacterial infections and can help differentiate between bacterial and viral infections [ 6 , 7 ]. Although elevated PCT serum concentrations are not exclusive to infections, PCT is still considered to be one of the best biomarkers available to diagnose sepsis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%